2019
DOI: 10.1002/ptr.6498
|View full text |Cite
|
Sign up to set email alerts
|

Isocordoin analogues promote apoptosis in human melanoma cells via Hsp70

Abstract: Isocordin 1 and a series of 4‐oxyalkyl‐isocordoin analogues 2–8 were evaluated for their cytotoxicity effect against human melanoma cells (A2058). Analogues 4, 5, and 6 showed a higher inhibitory activity with IC50 values of 12.91 ± 0.031, 24.88 ± 0.013, and 11.62 ± 0.017, respectively. These analogues, 4, 5, and 6, also induced an apoptotic response at 12.5‐ and 25‐μM concentrations. They inhibited the expression of antiapoptotic proteins Bcl‐2 and Hsp70, a critical factor that promotes tumour cell survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In another study, 24 patients with FD were randomized to receive either ginger or a placebo for 14 days. The study found that ginger significantly improved gastric emptying compared to a placebo [ 19 ]. However, a study involving 14 healthy adults found no significant effect of ginger on gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, 24 patients with FD were randomized to receive either ginger or a placebo for 14 days. The study found that ginger significantly improved gastric emptying compared to a placebo [ 19 ]. However, a study involving 14 healthy adults found no significant effect of ginger on gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…The study included 60 patients who were randomized to receive either ginger or a PPI for four weeks. Both treatments were effective in reducing symptoms of dyspepsia, including epigastric discomfort, with no significant difference between the two groups [ 19 ]. A report from a systematic review of randomized controlled trials (RCTs) found that ginger was more effective than a placebo in reducing symptoms of dyspepsia, including epigastric discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…In melanoma, circulating heat shock protein 70 (HSP70) as the primary effector of NLRP3 triggering a distant TLR4‐dependent signaling cascade (NLRP3‐HSP70‐TLR4 axis), regulates granulopoiesis and recruitment and the accumulation of PMN‐MDSCs in distant organs, thus supporting the creation of a premetastatic niche 23 . Furthermore, in the context of the well‐investigated anti‐apoptotic role in melanoma cells of HSP70, 24 the 78 kDa cell surface glucose‐regulated protein (csGRP78), as a member of the HSP70 family, is involved in autoimmune‐mediated activation of signaling pathways promoting cancer cell survival 25 . Concerning the presumed HSP90 role in melanoma, the scientific literature to date has been inconclusive.…”
Section: Introductionmentioning
confidence: 99%